2022
DOI: 10.1038/s41598-022-15496-w
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of postoperative cardiac events in multiple surgical cohorts using a multimodal and integrative decision support system

Abstract: Postoperative patients are at risk of life-threatening complications such as hemodynamic decompensation or arrhythmia. Automated detection of patients with such risks via a real-time clinical decision support system may provide opportunities for early and timely interventions that can significantly improve patient outcomes. We utilize multimodal features derived from digital signal processing techniques and tensor formation, as well as the electronic health record (EHR), to create machine learning models that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…AI applications also affect clinician outcomes, specifically, clinician decision making, clinician workflow and efficiency, and clinician evaluations and acceptance of AI applications. In this review, thirty-two studies reported clinician outcomes of AI in cardiac surgery (4,5,7,8,10,11,1338).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AI applications also affect clinician outcomes, specifically, clinician decision making, clinician workflow and efficiency, and clinician evaluations and acceptance of AI applications. In this review, thirty-two studies reported clinician outcomes of AI in cardiac surgery (4,5,7,8,10,11,1338).…”
Section: Resultsmentioning
confidence: 99%
“…Clinicians could potentially be guided by AI applications in making better medical decisions. Eighteen studies reported that AI applications can support clinician decision making (4,7,10,13,16,17,19,21,23,24,26,28,(30)(31)(32)(33)35,38). Machine learning models improve clinician's medical decisions by providing better preoperative risk assessment, stratification and prognostication (10,17,21,24,(30)(31)(32)35,38).…”
Section: B Clinician Outcomesmentioning
confidence: 99%
“…• Personalized decision-making: VLMs can be used to create multimodal learning models that predict postoperative deterioration events in surgical intensive care unit patients for precise early intervention by utilizing multimodal features from physiological signals and EHR data. 67,68 • Monitoring patients: VLMs can be used to monitor patients in a remote-monitoring care setting. For example, the integration of data from noninvasive devices such as smartwatches or bands with data from EHRs and other sensors, can be used to improve the reliability of fall detection systems 69 and gait analysis performance.…”
Section: Potential Clinical Applications Of Vlmsmentioning
confidence: 99%
“…VLMs have the potential to be a powerful tool for a wide range of clinical applications. Some examples of the opportunities for these models in this field include: Personalized decision‐making : VLMs can be used to create multimodal learning models that predict postoperative deterioration events in surgical intensive care unit patients for precise early intervention by utilizing multimodal features from physiological signals and EHR data 67,68 Monitoring patients : VLMs can be used to monitor patients in a remote‐monitoring care setting.…”
Section: Large‐scale Vlmsmentioning
confidence: 99%
See 1 more Smart Citation